A case report of 29 year old male patient with breast carcinoma: diagnosed on fine needle aspiration cytology - Patel, Komal; Chaudhri, Pallavi; Patel, Siddhi M. (International Journal of Research in Medical Sciences, 2019)
Breast cancer has been considered a female dominated disease. Carcinoma of male breast is a rare disease representing 1% of all breast cancers and less than 1 % of all cancers in men. The mean age at presentation is mainly in sixties. We here present a case of male breast cancer presented at very young age of 29 years, diagnosed on fine needle aspiration which was confirmed later on histopathological examination.